Induction of ferroelectricity in nanoscale ZrO2/HfO2 bilayer thin films on Pt/Ti/SiO2/Si substrates. (15th August 2016) - Lu, Y.W.; Shieh, J.; Tsai, F.Y.
Abstract: Large ferroelectricity has been demonstrated in nanoscale bilayer thin films consisting of undoped ZrO2 and HfO2 layers on conventional Pt/Ti/SiO2 /Si substrates for the first time. The bilayer thin films had thicknesses between 7.5 and 18 nm and their crystalline phases, symmetry groups, polarization hystereses and composition depth profiles were characterized to understand the influence of the stacking order and thickness of the ZrO2 and HfO2 layers on ferroelectricity. Two factors: (1) effective confinement of the HfO2 layer by the ZrO2 layer and Si substrate to promote the ferroelectric orthorhombic phase and (2) reduction of the bulk characteristics of the ZrO2 and HfO2 layers to minimize the paraelectric monoclinic phase are the key to stable ferroelectricity with a large remanent polarization. These factors can be manipulated by the stacking order and thickness of the layers, and consequently, producing ferroelectric behaviors ranging from minor to fully developed hystereses. The undoped ZrO2 /HfO2 bilayer thin film is a simpler design and can be fabricated more easily compared to the doped HfO2 or solid solution Hf x Zr1- x O2 thin films reported in the literature, which require not only precise composition control but also the less available TiN electrodes for stable ferroelectricity. The chosen Pt/Ti/SiO2 /Si substrate for the ZrO2 /HfO2 bilayer thin films is readily available and has been widely used in MEMS applications. These advantages make the ZrO2 /HfO2 bilayer thin films favorable for silicon-based device integration. Graphical abstract: